‘NABIO808’ (Syn. ‘NAROBAN5’): A tasty cooking banana cultivar with resistance to pests and diseases - Tumuhimbise, Robooni; Buregyeya, Henry; Kubiriba, Jerome; Tushemereirwe, Wilberforce K.; Barekye, Alex; Tendo, Reuben S.; Namagembe, Betty; Muhangi, Sedrach; Kazigye, Francis; Talengera, David; Tindamanyire, Jimmy; Akankwasa, Kenneth; et al. (Crop Breeding and Applied Biotechnology, 2019)
‘NABIO808’ is a newly released, conventionally-bred triploid cooking banana cultivar in Uganda. It produces an average bunch yield of 54.5 t ha-1 yr-1 and is resistant to weevils, nematodes, and black Sigatoka. Additionally, its food is yellow, soft, and tasty, like that of most preferred landrace cultivars, making it more acceptable to end-users.
Keywords: Matooke breeding; Host plant resistance; Weevils; Nematodes; Black Sigatoka